DUF1005 Family Identification, Evolution Analysis in Plants, and Primary Root Elongation Regulation of CiDUF1005 From Caragana intermedia - Tian, Xiaona; Niu, Xiaocui; Chang, Ziru; Zhang, Xiujuan; Wang, Ruigang; Yang, Qi; Li, Guojing (Frontiers in Genetics, 2022)
Domain of unknown function (DUF) proteins represent a number of gene families that encode functionally uncharacterized proteins in eukaryotes. Among them, DUF1005 family members in plants possess a 444 amino-acid conserved domain, and this family has not been described previously. In this study, a total of 302 high-confidence DUF1005 family members were identified from 58 land plant species, and none was found from the four selected algae. Thus, this finding manifested that DUF1005s might belong to a kind of land plant-specific gene family, which originated by the landing of plants, and no expansion of this family has happened from evolution. Phylogenetic analysis showed that the DUF1005 family genes can be classified into four subgroups in 58 land plant species. The earliest emergence Group I, including a total of 100 gene sequences,exists in most species spanning from mosses to seed plants. Group II and Group III, with 69 and 74 genes respectively, are belonging to angiosperms. Finally, Group IV is the last batch of genes to emerge, with 59 members, and is a unique in only dicotyledons. Expression pattern analysis of CiDUF1005, a member of DUF1005 family from Caragana intermedia, showed that the CiDUF1005 genes are differentially regulated under various stresses. Transgenic lines with heterologous expression of CiDUF1005 in Arabidopsis thaliana had longer primary roots and more lateral roots than the wild-type. These results expanded our knowledge of the evolution of the DUF1005 family in plants and will contribute to the elucidation of biological function of the DUF1005 family in the future.